2017
DOI: 10.18203/2349-3291.ijcp20173765
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and pattern of respiratory diseases in children

Abstract: Background: Respiratory tract infections are a major cause of   morbidity and mortality in children. Therefore, it is imperative that research studies be conducted to determine the pattern of respiratory diseases in the pediatric age group. Present study was done to determine the outcome, frequency and pattern of respiratory infections in children admitted in a tertiary care hospital.Methods: This prospective, cross-sectional study was conducted from September 2014 to February 2016. Data was analyzed on SPSS 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…Local data from Karachi revealed bronchopneumonia to be the most common disease (62.9%) requiring admission among children. 18 A study by Oguonu T et al revealed 29.1% children to have pneumonia which is very close to what we noted. 6 In a study from Nigeria, Ibraheem RM et al noted pneumonia to be the cause of admission in almost half of the children.…”
Section: Resultssupporting
confidence: 91%
“…Local data from Karachi revealed bronchopneumonia to be the most common disease (62.9%) requiring admission among children. 18 A study by Oguonu T et al revealed 29.1% children to have pneumonia which is very close to what we noted. 6 In a study from Nigeria, Ibraheem RM et al noted pneumonia to be the cause of admission in almost half of the children.…”
Section: Resultssupporting
confidence: 91%
“…Our study revealed a slight male predominance (54%) and infants were the vulnerable population for respiratory illness which is in keeping with other studies [9][10][11][12][13][14][15][16][17][18][19] . This may be due to less mature immune system making the infant more susceptible to respiratory infections.…”
Section: Discussionsupporting
confidence: 92%
“…Admissions due to respiratory illness accounted for 31% of hospital admissions. This is similar to studies done in other areas of Sri Lanka as well as worldwide where the admissions due to respiratory illness ranged from 25-35% [9][10][11][12][13][14][15][16][17][18][19] . According to the 2017 Annual Health Statistics, Sri Lanka, respiratory illnesses are in the 4 th rank both in hospital admissions and in mortality 1 .…”
Section: Discussionsupporting
confidence: 88%
“…It consists of 12 primary health care facilities and one tertiary and one district headquarter hospitals. Acute respiratory infections cases are more common during the winter season in Pakistan ( 13 ).…”
Section: Methodsmentioning
confidence: 99%